Towards a typology of consumer–brand interactions on Facebook - Machado, Joana César (2016)
Facebook has become a key player in branding activities. However empirical research on consumer–brand interaction on Facebook is still in its infancy. The aim of this research is to provide additional insights to brand managers on how to increase consumers’ interaction with brands on Facebook. We develop a new typology of consumers based on consumer motivations to interact with brands on Facebook and explore these interactions. Building on the five motivations that influence consumers’ interactions, a classification using clustering techniques reveals four different groups of consumers: “brand detached”, “brand profiteers”, “brand companions” and “brand reliants”. Our results provide valuable insights, assisting brand managers in developing strategies for effectively reaching the most desirable groups of consumers.